STEGANOGRAPHIC SECRET COMMUNICATION USING RGB PIXEL ENCODING AND CRYPTOGRAPHIC SECURITY - Ghulam Gilanie; Syeda Naila Batool; Syed Naseem Abbas; Akkahsha Latif; Muhammad Iqbal; Hina Shafique; Sana Cheema (Spectrum of Engineering Sciences, 2025)
This research presents an advanced and highly practical strategy for secure communication through steganography, leveraging RGB pixel encoding and cryptographic security. Our novel methodology segments message data into 3-bit, 3- bit, and 2-bit components, which are seamlessly integrated with the corresponding RGB pixel values of a digital image. This structured embedding process generates a logarithmic (LOG) table, which is subsequently encrypted using the Rijndael Managed algorithm, enhancing both confidentiality and resistance to cryptographic attacks. Comparative analysis demonstrates that our approach maintains image quality with less than a 1% variation in pixel intensity, significantly outperforming traditional steganographic techniques such as the Least Significant Bit (LSB) method. The proposed method establishes a robust and imperceptible communication channel, offering superior security, undetectability, and resilience against steganalysis.